Immune Response Against Sporothrix schenckii in TLR-4-Deficient Mice - Sassa, Micheli Fernanda [UNESP]; Ferreira, Lucas Souza [UNESP]; de Abreu Ribeiro, Livia Carolina [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Springer, 2012)
For many fungal diseases, macrophages are the major cell population implicated in host protection, primarily by their ability to eliminate the invading fungal pathogen through phagocytosis. In sporotrichosis, this remains true, because of macrophages' ability to recognize Sporothrix schenckii through specific receptors for some of the fungus' cellular surface constituents. Further confirmation for macrophages' pivotal role in fungal diseases came with the identification of toll-like receptors, and the subsequent numerous associations found between TLR-4 deficiency and host susceptibility to diverse fungal pathogens. Involvement of TLR-4 in immune response against sporotrichosis has been conducted to investigate how TLR-4 signaling could affect inflammatory response development through evaluation of H2O2 production and IL-1 beta, IL-6 and TGF-beta release during the course of S. schenckii infection on TLR-4-deficient mice. The results showed that macrophages are largely dependent on TLR-4 for inflammatory activation and that in the absence of TLR-4 signaling, increased TGF-beta release may be one of the contributing factors for the abrogated inflammatory activation of peritoneal exudate cells during mice sporotrichosis.
Keywords: Sporothrix schenckii; TLR-4; TGF-beta; Cytokines; Macrophages